MALNUTRITION IN OLDER ADULTS AND ITS CORRELATES WITH ANXIETY AND DEPRESSION - Deklāva, Liāna; Vilka, Lolita; Millere, Inga; Fokina, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Elderly research suggests inappropriate food intake as a one of the health issue. Malnutrition may have an undesirable effect on the health of the body. Elderly people are most at risk because they are often the result of loss of appetite, difficulties with daily shopping, meal preparation, somatic disorders and mental disorders such as depression. The purpose of the study was to investigate malnutrition among the elderly who are staying in social care institutions and to assess its association with anxiety and depression. The data from the study were obtained using the Universal Malnutrition Screening, Geriatric Alert Scale and the Geriatric Depression Scale as tools. Overall, 102 respondents from two social care institutions participated in the study. The majority were women 64.7% (35.3% were male). Respondents ranged in age from 65 to 91 years. There were 27.44% of participants with malnutrition risk and 45.10% with signs of anxiety. Depression symptoms were detected 60.78% of respondents. Within the research sample, a statistically significant relationship between malnutrition and depression was found (r = 0.302, p< 0.01). Prevention of malnutrition and the early detection of depression among seniors will contribute to the improvement of the quality of their life and quality of health care.